2021
DOI: 10.3390/fermentation7030136
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipid Biosurfactant Production from Waste Cooking Oils by Yeast: Review of Substrates, Producers and Products

Abstract: Biosurfactants are a microbially synthesized alternative to synthetic surfactants, one of the most important bulk chemicals. Some yeast species are proven to be exceptional biosurfactant producers, while others are emerging producers. A set of factors affects the type, amount, and properties of the biosurfactant produced, as well as the environmental impact and costs of biosurfactant’s production. Exploring waste cooking oil as a substrate for biosurfactants’ production serves as an effective cost-cutting stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(16 citation statements)
references
References 135 publications
0
16
0
Order By: Relevance
“…To lower the production cost many of the researcher have suggested application of agro-industrial waste as the chief carbohydrate source. 157 Though a huge number of studies are established using glucose, glycerol, acetates and other organic acids and n -alkanes which all are very costly and cannot reduce the cost of production. The investigation on production of mannosylerythritol lipids (MEL) by C. antarctica using n -alkanes as carbon sources reported that the chain length of the alkane substrate efficiently influence the productivity of MEL; highest yield obtained from n -octadecane.…”
Section: Influence Of Factors In Biosurfactant Production and Medium ...mentioning
confidence: 99%
“…To lower the production cost many of the researcher have suggested application of agro-industrial waste as the chief carbohydrate source. 157 Though a huge number of studies are established using glucose, glycerol, acetates and other organic acids and n -alkanes which all are very costly and cannot reduce the cost of production. The investigation on production of mannosylerythritol lipids (MEL) by C. antarctica using n -alkanes as carbon sources reported that the chain length of the alkane substrate efficiently influence the productivity of MEL; highest yield obtained from n -octadecane.…”
Section: Influence Of Factors In Biosurfactant Production and Medium ...mentioning
confidence: 99%
“…With increased knowledge of bioeconomy and circular economy globally, the search for waste as feedstock and renewable bioresources and has intensified greatly across various industries including biosurfactant production [19].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…As they are of microbial origin and demonstrate a series of interesting characteristics such as low toxicity, pH tolerance, temperature, ionic strength, biodegradability, antimicrobial activity, and emulsifying and demulsifying capacity, these polymers become of great interest in applications in food, cosmetics, and advanced bioremediation processes, including in drug delivery [83]. Candida lipolytica [46] Refinery oil waste Yeast Glycolipid [33,77,89] These agents have several properties suitable for the food industry as emulsifiers in the processing of raw materials, indispensable for food products that require stability content, a characteristic sensory pattern, and longer shelf life, being applied from products derived from meat, milk, and their derivatives. Given their antimicrobial and anti-adhesive properties, these biosurfactants directly contribute to reducing contamination of processed foods [92].…”
Section: Applicationsmentioning
confidence: 99%